SMART POLICE: SOLUSI ATAS LAW ENFORCEMENT TERHADAP PELANGGARAN LALU LINTAS DALAM MEWUJUDKAN INDONESIA YANG BERINTEGRITAS - Hardiani, Leni; Lenni (UKM Lembaga Penalaran dan Penulisan Karya Ilmiah Fakultas Hukum Universitas Hasanuddin, 2024)
Traffic violations often occur in Indonesian in due to low public awareness of traffic rules, leading to congestion and accidents with material losses reaching trillions of rupiah Indonesian. This study aims to outline the regulations governing traffic law enforcement in Indonesian and to project how Smart Police technology can enhance enforcement of traffic violations, contributing to a more integrated Indonesian. The study uses a normative method with a legislative approach, utilizing secondary data from various literature sources, which are then analyzed deductively to examine the legal rules and topics addressed. Law No. 22/2009 (LLAJ Law) on Road Traffic and Transportation emphasizes that traffic order can create a safe environment and stresses the importance of awareness and discipline among road users. Smart Police technology can support law enforcement more effectively by aiding in the monitoring and addressing of traffic violations quickly and accurately. Designed to maintain order on the roads, Smart Police enhances driver safety through its real-time detection and prevention capabilities. Equipped with artificial intelligence, specialized security features, and other functionalities, Smart Police improves interaction with motorists and connects directly with law enforcement for more efficient legal enforcement. It represents an innovative solution for improving driving safety and public order.